2007
DOI: 10.1021/bi700865e
|View full text |Cite
|
Sign up to set email alerts
|

NMR Investigation of Primer-Template Models:  Structural Effect of Sequence Downstream of a Thymine Template on Mutagenesis in DNA Replication

Abstract: Misaligned structures can occur in primer-templates during DNA replication, which can be bypassed and extended by low-fidelity polymerases and ultimately lead to mutations. In this study, we have investigated how the nucleotide downstream of a thymine template affects the primer-template structures upon misincorporation of dNTPs. The base pair structures at the replicating sites of a set of primer-template models containing either a G or an A downstream of the thymine template have been determined using NMR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 42 publications
(52 reference statements)
9
27
0
Order By: Relevance
“…2C) indicate the formation of a C17 · G4 Watson–Crick base pair, confirming the misaligned structures with a Sp‐bulge and a closing C · G Watson–Crick base pair. This structural finding is similar to our previous observations on misaligned structures with a T‐bulge [17,18] or C‐bulge [19] in pyrimidine templates.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2C) indicate the formation of a C17 · G4 Watson–Crick base pair, confirming the misaligned structures with a Sp‐bulge and a closing C · G Watson–Crick base pair. This structural finding is similar to our previous observations on misaligned structures with a T‐bulge [17,18] or C‐bulge [19] in pyrimidine templates.…”
Section: Resultssupporting
confidence: 92%
“…Despite the presence of lesions can slow or stall the action of polymerase, low fidelity DNA polymerases have shown the capability to accommodate misaligned primer–template in their loose active sites [15,16], and thus, DNA replication can continue and deletion error can occur. Recently, we have demonstrated that misalignment can occur at the replicating sites of primer–templates [17–19], yet the structural effect of Sp and oG lesions at these sites remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…DNA mismatches can occur in vivo due to the following reasons: (i) misincorporation of bases [24] or strand misalignment [25][26][27][28][29] during replication, (ii) heteroduplex formation during homologous recombination [30], and (iii) spontaneous deamination [31] and damage by mutagenic chemicals or ionizing radiation [32][33][34][35][36]. Results from various research groups have shown that the mismatch repair efficiency depends on the type of mismatches and base composition of neighboring sequences [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Structural studies of DNA mismatches become more and more important as they have been found to occur in the double-helical stem regions of the unusual secondary structure formed by highly mutagenic and disease-related sequences [39][40][41]. These mismatches can occur in vivo during DNA replication [42][43][44][45][46][47], recombination [48], or as a result of DNA damage [49][50][51][52][53]. If left unrepaired, mismatched sites are highly mutagenic [54].…”
Section: Introductionmentioning
confidence: 99%